Journey through the India’s National Education Policy – Previous and the Present - PALLATHADKA, HARIKUMAR; MANOHARMAYUM, DOLPRIYA DEVI; PALLATHADKA, LAXMI KIRANA; MAKKI, VASISTA RAMA RANJAN (The journal of contemporary issues in business and government, 2021)
Education in India has seen a frequent change from the history to the present. Education is not just learning the subjects like history, economics, mathematics, science, et cetera, but gaining relevant skills. Education helps to utilize resources successfully. Through the enhancement of education, individuals can gain knowledge and skills related to each subject. Through the development of education, a country can foster resources, and development can be achieved. India has now come up with new policies related to the education sector. Journey through the national education policy provides an overall view of all the policies which were introduced in India. At the same time, it showcases various committees and commissions set up to provide a better educational facility. In this particular research article, an outlook is provided over the meaning and the need of education policy. It also focuses on three major national education policies introduced by the Government of India in the previous years of 1968, 1986, and 2020. This article compares the objectives and other important factors of the three national education policies that have succeeded in bringing changes in the education sector from time to time.